Hubungan Kecerdasan Emosi dengan Self-Efficacy pada Sarjana Fresh Graduate di Daerah Istimewa Yogyakarta (DIY) - Mu'affi, Oktavia; Pusvitasari, Putri (Jurnal Ilmiah Psikomuda (JIPM) Connectedness, 2024)
After graduating from college, fresh graduates will generally begin a transition phase of life. Fresh graduates hope to be able to work according to the field and expertise they have. However, these hopes do not always come true, in reality fresh graduates find it difficult to find work. Lack of self-confidence and difficulty controlling emotional intelligence in fresh graduates after graduation, results in unpreparedness to face the world of work. Thus, the emotional intelligence of fresh graduates is not well controlled. The aim of this research is to determine the relationship between emotional intelligence and self-efficacy in fresh graduates. The subjects in this study were 64 female or male fresh graduates. Using purposive sampling technique. The method used in this research uses quantitative methods with a correlational approach. The data collection tool uses an emotional intelligence. Normality test, linearity test, and associative hypothesis test. The data analysis method used in this research is Spearman Rho analysis which was tested using SPSS 23 for Windows. The results of the analysis show that the emotional intelligence variable is not correlated and is not significant with self-efficacy (r = 0.087, p = 0.492). These results indicate that the research hypothesis is rejected, there is no relationship between emotional intelligence and self-efficacy.